Analisis DER, EPS, ROA, ROE, dan NPM Terhadap Harga Saham Perusahaan Manufaktur Subsektor Makanan dan Minuman di Bei Tahun 2019-2023 - Astriana Dewi; Badrus Zaman; Diah Nurdiwaty (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
The research was conducted to determine the influence of Debt to Equity Ratio, Earning Per Share, Ratio on Asset, Ratio on Equity, Net Profit Margin, on the share prices of Food and Beverage Subsector Manufacturing Companies listed on the Indonesia Stock Exchange in 2019-2023.The population in this study are all financial reports of manufacturing companies in the food and beverage sub-sector for 2019-2023 which were published on the website www idx.co.id. The research sample was taken based on a purposive sampling technique. In this study, the research samples were 35 financial reports. Data analysis uses multiple linear regression analysis.The research results show that partially the DER variable has a significant effect on stock prices with a significance value of 0.05 < 0.020. The EPS variable has no significant effect on share prices with a significance value of 0.05 > 0.973. The ROA variable has no significant effect on share prices with a significance value of 0.05 > 0.904. The ROE variable has a significant effect on share prices with a significance value of 0.05 < 0.000. Simultaneously the variables DER, EPS, ROA, ROE, and NPM have a significant effect on share prices, this can be seen from the probability value of 0.000 or the probability value <0.05. With a simultaneous coefficient of determination of 57.1%.